Determination of Parasitic Contamination in Vegetables Collected from Local Markets in İzmir Province, Türkiye - Bilgiç, Fatma; Akdur Ozturk, Eylem; Babat, Sefer Özer; Babao?lu, Aylin; Dirim Erdo?an, Derya; Korkmaz, Metin (Galenos Publishing House, 2023)
Objective: Fresh vegetables are an important part of a healthy and nutrient-rich diet but the consumption of raw vegetables without proper washing is the main way for transmission of parasites. This study was aimed at determining the rate of parasitic contamination in prewashed fresh vegetables sold at randomly selected 10 retail markets which is the last step to reach the consumer in İzmir, Türkiye. Methods: A total of 80 samples selected from eight types of vegetables including tomato, spinach, lettuce, rocket, mint, parsley, dill, and cucumber were examined for parasitic agents microscopically by sedimentation method after washing samples with normal saline. Statistical analysis was performed using SPSS software version 20.0. Results: Protozoan cysts, helminth eggs, and larvae were detected in 21 (26.2%) of 80 samples from eight different vegetable species. Rhabditidiform larvae 18.7%, Blastocystis spp. 5%, Toxocara spp. 2.5%; Ascaris spp., Fasciola spp., Entamoeba histolytica/ Entamoeba dispar and hooked worms were found in 1.2%. Spinach and mint samples were contaminated with parasites significantly more than other fresh vegetable samples (p<0.008, odds ratio =80.0; p<0.017, odds ratio =46.6 respectively). Cruznema spp., a plant nematode, was found at the highest rate according to the results of culture, polymerase chain reaction and sequencing, respectively. Conclusion: In this study, the parasitic contamination was found in approximately one of the four vegetables sold in randomly selected markets in İzmir. These findings show that vegetables sold in local markets can cause parasitic infections if they are consumed without adequate washing and awareness should be raised on this issue. In addition, it was concluded that morphological examinations should be confirmed by molecular studies and sequencing as much as possible in order to avoid misdiagnosis of rhabditidiform larvae. © 2023, Galenos Publishing House. All rights reserved.
Türkiye’nin İzmir İlindeki Yerel Marketlerden Toplanan Sebzelerdeki Parazit Bulaşının Belirlenmesi
Keywords: parasitic contamination; Türkiye; Vegetable; İzmir